Analisis Relasi Makna Dalam Lirik Lagu ‘Runtuh’ Karya Feby Putri Dan Fiersa Besari - Sianipar, Ratna Lolane; Sigab, Ribka Elstin; Siagian, Arlin Septia Basana; Pasaribu, Kristin Dwi Amsari; Puteri, Anggia (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the relationship of meaning contained in the lyrics of the song